Amniotic fluid paraoxonase-1 activity, thyroid hormone concentration and oxidant status in neural tube defects - Sak, Sibel; Agacayak, Elif; Tunc, Senem Yaman; Icen, Mehmet Sait; Findik, Fatih Mehmet; Sak, Muhammet Erdal; Yalinkaya, Ahmet; Gul, Talip (The journal of obstetrics and gynaecology research, 2016)
Aim The aim of this study was to investigate the potential association between neural tube defects and paraoxonase‐1 activity in amniotic fluid. We studied total oxidant status, total antioxidant capacity, paraoxonase‐1 activity and thyroid hormone amniotic fluid concentration in fetuses with neural tube defects. Methods The present study was performed at the Department of Obstetrics and Gynaecology and the Department of Clinical Biochemistry of Dicle University between September 2011 and June 2013. The study group included 37 amniotic fluid samples from pregnant women (16–20 weeks of gestation) with fetuses affected by neural tube defects. The control group consisted of 36 pregnant women who were diagnosed with a high‐risk pregnancy according to first or second trimester aneuploidy screening and were later confirmed on amniocentesis to have genetically normal fetuses. Results Amniotic fluid paraoxonase‐1 activity and total oxidant status were significantly higher (P = 0.023, P = 0.029, respectively) whereas free T4 was significantly lower (P = 0.022) in fetuses with neural tube defects compared with control subjects. In fetuses with neural tube defects, amniotic fluid paraoxonase‐1 activity correlated positively with total oxidant status (r = 0.424**, P = 0.010), and amniotic fluid total antioxidant capacity correlated positively with free t4 (r = 0.381*, P = 0.022). Conclusion This is the first study in the literature to show an association between paraoxonase‐1 activity and thyroid hormone concentration and neural tube defects.